Emporion (Empúries – L´Escala), Spanien. Der Architekturdekor von Emporion. Untersuchungen zum Baudekor der griechischen und römischen Stadt. Die Arbeiten der Jahre 2019 bis 2021 - Gans, Ulrich-Walter (e-Forschungsberichte des DAI, 2021)
The largest Greek settlement on the Iberian Peninsula was the coastal town of Emporion. After the Second Punic War, it was also settled by the Romans and continuously expanded. Significant evidence of monumental and residential buildings has been preserved from both cultures. The project »EMPORION« explores the ornamental and figurative decoration of this architecture. There are around 350 large-format objects. These not only provide information of the dating and evaluation of the buildings, but also of the development of the Emporion. In addition, they have an informative value for the art and cultural-historical development of the western Mediterranean area in general.